2006
DOI: 10.1097/01.ico.0000208824.55485.6a
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hydrops in Keratoconus Masquerading as Acute Corneal Transplant Rejection

Abstract: It is important to differentiate hydrops of the host cornea from acute transplant rejection. This distinction will allow the judicious use of steroids and may allay patient anxiety about possible rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…the DM, scrolling of the free edges, and stromal edema. These findings are similar to those in patients with hydrops in non transplanted corneas [5].…”
Section: Casesupporting
confidence: 89%
See 1 more Smart Citation
“…the DM, scrolling of the free edges, and stromal edema. These findings are similar to those in patients with hydrops in non transplanted corneas [5].…”
Section: Casesupporting
confidence: 89%
“…Wickremasinghe, et al [5] looked at the histology of the donor button in patients who had hydrops after PKP, which revealed breaks in…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, it can occur in a corneal graft and is frequently an extension of a break in Descemet's membrane from the host cornea to the donor graft. This has been reported in two separate case reports 23…”
Section: Introductionmentioning
confidence: 58%
“…Lyon et al [3] reported a case of acute hydrops localized in a corneal graft. The remaining five cases developed in the area of the graft-host interface, and corneal edema extended to both the graft and the host cornea [1,2,4]. The onset of hydrops in all six cases occurred between 19 and 33 years after PKP.…”
Section: Commentmentioning
confidence: 94%
“…Only six cases of hydrops after PKP have been reported [1][2][3][4]. Lyon et al [3] reported a case of acute hydrops localized in a corneal graft.…”
Section: Commentmentioning
confidence: 97%